Multifunctional Composite Nanofibers (Journal of Fiber Bioengineering and Informatics, 2013)
Multi-functional fibrous materials are a new family of fiber materials whose physical and chemicalproperties are sensitive to the change in the environment such as temperature, pressure, electric field,magnetic field, optical wavelength, adsorbed gas molecules and the pH value. This paper introduces a newapproach to translate functions from nanoparticles to advanced fibrous structures by co-electrospinningof composite nanofibers. To illustrate this composite nanofiber concept an example of nanofibers thathave tailorable, electrical and magnetic functions is shown.
Keywords: Functional Materials; Nanofibers; Co-electrospinning; Nanocomposite; Lignin Nanofiber